Comparison between photoplethysmographic heart rate monitor from Polar Vantage M and Polar V800 with H10 chest strap while running on a treadmill: Validation of the Polar Precision PrimeTM photoplestimographic system - Ruiz-Malagón, E. J.; Ruiz-Alias, S. A.; García-Pinillos, F.; Delgado-García, G.; Soto-Hermoso, V. M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Chest bands have been the most used device to monitor heart rate during running. However, some runners feel uncomfortable with the use of bands due to the friction and pressure exerted on the chest. Thus, the aim of this study was to determine if the photoplethysmography (PPG) system Polar Precision Prime used in the Polar Vantage M watch could replace chest bands (Polar V800-H10) to monitor heart rate with the same precision. A group of 37 people, middle-distance and long-distance professional runners, participated in this study. The submaximal speed was determined using 50% of the participants` maximum speed in the height of their season. The Polar Vantage M reported high correlation (r > 0.84) and high ICC (ICC > 0.86) when comparing its heart rate monitor with the Polar V800 synchronised with H10 chest strap during recording intervals of more than 2 min. The systematic bias and random error were very small (<1 bpm), especially for the 600 s recording interval (0.26 ± 5.10 bpm). Nevertheless, the error increased for 10 s (-5.13 ± 9.20 bpm), 20 s (-8.65 ± 12.60 bpm) and 30 s (-10.71 ± 14.99 bpm) time intervals. In conclusion, the PPG Polar Precision Prime included in the Polar Vantage M demonstrates that it could be a valid alternative to chest bands for monitoring heart rate while running, taking into account some usage considerations, good strap adjustment and an initial calibration time during the first 2-3 min.